Quercus ilex resprouts after fire: response to photoinhibition. (PLANT PHYSIOLOGY, 1997)
The study was located on Serra del Garraf mountains, Barcelona, NE Spain, overlooking the Mediterranian sea at 530 m. On August 1995 a wild fire consumed 100 hectares of the forest. In spring 1996 four plots were set (100 x
APS